Accelerating genetic gain through early-stage on-farm sparse testing - Werner, Christian; Zaman-Allah, Mainassara; Assefa, Teshale; Cairns, Jill E.; Atlin, Gary N. (Elsevier, 2025)
Most African crop breeding programs conduct early-stage selection at very few research stations, which may not reflect smallholder farm conditions. Early-stage on-farm sparse testing utilizes genomic relationships to shift selection from research stations to hundreds of farms in the target population of environments, facilitating increased genetic gain in farmers’ fields.